The Effect of Product Quality and Service Quality on Customer Satisfaction in TikTok Shop: The Mediating Role of Brand Image - Ahmad Yusuf Fauzan Simanjuntak; Suparman J Siburian; Bryan Carlos Yeremia Pardede; Jamaluddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to examine the effects of product quality and service quality on customer satisfaction in TikTok Shop, with brand image serving as a mediating variable. This study employed a quantitative research approach. The population consisted of active students in North Sumatra who had purchased products through TikTok Shop. Using purposive sampling, 400 respondents were selected. Data were collected through an online questionnaire measured on a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS. The findings reveal that brand image has a positive and significant effect on customer satisfaction. Service quality also has a positive and significant effect on both brand image and customer satisfaction. In contrast, product quality does not have a significant effect on either brand image or customer satisfaction. Furthermore, brand image significantly mediates the relationship between service quality and customer satisfaction, but it does not mediate the relationship between product quality and customer satisfaction. These results suggest that service quality and brand image shape customer satisfaction in TikTok Shop more strongly than product quality. This suggests that, within the social commerce context, consumers place greater emphasis on service experience and digital brand perception in evaluating satisfaction. This study is limited to active students in North Sumatra and focuses only on product quality, service quality, brand image, and customer satisfaction. This study enriches the literature on social commerce by highlighting the dominant role of service quality and brand image in explaining customer satisfaction on TikTok Shop and offers practical insights for sellers in enhancing customer experience and strengthening brand image.